Advancements in 5G-Enabled Industrial IoT: Emerging Applications and Future Research Directions - Joe Laksamana Silitonga (International Journal of Information System and Innovative Technology, 2024)
The emergence of 5G technology has significantly transformed the Industrial Internet of Things (IIoT) by enabling high-speed, low-latency, and ultra-reliable communication. This advancement has paved the way for smarter and more efficient industrial operations, including automated manufacturing, predictive maintenance, and real-time monitoring. By leveraging key features such as network slicing, massive machine-type communication (mMTC), and ultra-reliable low-latency communication (URLLC), industries can enhance operational efficiency, reduce downtime, and optimize resource management. Despite these advantages, several challenges hinder the full-scale deployment of 5G-enabled IIoT. Issues such as scalability constraints, security risks, interoperability challenges, and high infrastructure costs continue to pose barriers. Additionally, integrating 5G with existing industrial systems and ensuring efficient spectrum utilization require innovative solutions. Addressing these concerns necessitates advancements in AI-driven network management, robust cybersecurity frameworks, and optimized communication protocols. This paper presents a comprehensive review of the current landscape of 5G-enabled IIoT, exploring state-of-the-art research on network architectures, edge computing, AI integration, and security mechanisms. Furthermore, it identifies future research directions, emphasizing the role of intelligent networking, autonomous decision-making, and sustainable infrastructure in advancing IIoT applications. The insights provided in this review aim to support researchers and industry practitioners in optimizing 5G-powered IIoT ecosystems.